Change in choroidal thickness after intravitreal injection for treatment of neovascular age-related macular degeneration: Ranibizumab versus aflibercept - Kaya, Faruk (Masson Editeur, 2017)
Purpose. - To compare the changes in subfoveal choroidal thickness after intravitreal ranibizumab or aflibercept injections for neovascular age-related macular degeneration (nAMD).Methods. - In this retrospective study, 28 eyes with nAMD treated with 3 consecutive monthly injections of ranibizumab (IVR) and 24 eyes with nAMD treated with 3 consecutive monthly injections of aflibercept (IVA) between September 2012 and June 2016 were reviewed. The follow-up time was 6 months. Changes in two groups' best-corrected visual acuity (BCVA) and subfoveal choroidal thickness by using enhanced depth imaging optical coherence tomography at 1st, 3rd and 6th months were recorded and compared.Results. - Choroidal thickness decreased significantly in eyes treated with IVR (P=0.015, 0.01 and 0.01, respectively) or IVA (P=0.001, 0.001 and < 0.001, respectively) at 1, 3 and 6 months examination but IVA treated eyes presented a significantly further reduction in choroidal thickness when compared with ranibizumab (P=0.03, 0,04 and 0.03, respectively). There was no significant difference between aflibercept and ranibizumab group when change in BCVA from baseline compared at 1, 3 and 6th months (P=0.54, 0.06 and 0.37, respectively). There was no correlation between change in choroidal thickness and the BCVA outcomes in either group.Conclusions. - Subfoveal choroidat thickness decreased significantly after both of IVR and IVA injections in patients with nAMD. In conclusion, intravitreal injections of ranibizumab or aflibercept affect not only neovascular lesion but also the underlying choroid.
Keywords: Ranibizumab; Aflibercept; Choroidal Thickness; Neovascular Age-Related Macular Degeneration